Atypical symptoms and health‐related quality of life of patients with asymptomatic reflux esophagitis. (March 2015) - Tomita, Toshihiko; Yasuda, Toshinari; Oka, Hideo; Terao, Shuichi; Arai, Eitastu; Oshima, Tadayuki; Fukui, Hirokazu; Hori, Kazutoshi; Watari, Jiro; Miwa, Hiroto
Abstract: Background and Aim: Asymptomatic reflux esophagitis (RE) is simply regarded as RE without the typical reflux symptoms, but it is unknown whether patients with asymptomatic RE have atypical symptoms. The aim of this study was to examine the clinical characteristics and health‐related quality of life (HRQOL) of patients with asymptomatic RE. Patients and Methods: Consecutive patients with RE were enrolled during January 2010 to August 2012, and of them, 41 who had taken acid‐suppressing drugs were excluded, leaving 280 patients as the study group. The patients' symptoms were evaluated using a self‐completed questionnaire (modified Frequency Scale for the Symptoms of gastroesophageal reflux disease [FSSG]), as well as an HRQOL questionnaire (SF‐8). We defined the typical symptoms of RE as heartburn and regurgitation. Asymptomatic RE was defined if the total symptom score was 0 or the minimum (1 point) for typical reflux symptoms in the modified FSSG. Results: Of the 280 RE patients, 71.8% ( n = 201) were symptomatic and 28.2% ( n = 79) were asymptomatic. The atypical symptom scores were significantly lower in asymptomatic RE (2.2 ± 2.2) than in symptomatic RE patients (6.9 ± 5.2) ( P < 0.0001), and the HRQOL scores were significantly higher in asymptomatic RE than in symptomatic RE ( P < 0.0001). Sleep was significantly less disturbed and chronic cough less frequent in asymptomatic RE than in symptomatic RE. Conclusion: Frequency and severity of atypical symptoms in patients with asymptomatic RE were significantly less than in patients with symptomatic RE, and the HRQOL score was significantly higher in those patients. These observations suggest a specific patient cohort that is truly unlikely to manifest symptoms.